Aceitação do uso de tecnologia : fatores que influenciam servidores públicos de uma instituição federal de ensino a utilizarem um sistema de informação - Souza, Maísle Alves Moraes de (2014)
The adoption of information systems (IS) by public organizations it is currently a need to restructure its management activities. From this adoption, there is an expectation that users of SI satisfactorily use the benefits to your work activities. However, there is a gap in the related resistance to change and resource use of information technology (IT) public sector. Thus, understanding the factors that influence their users to accept or use of this new technology represents a significant research purpose, both for the academy and for public management. Thus, the main objective of this dissertation is to investigate factors of technology acceptance and use that influencing public servants of a Federal Institution of Education, particularly the Federal University of Sergipe, to use an information system. Studies have shown the existence of several factors that influence the acceptance and use of technology and, considering the purpose of this research, the model UTAUT (Unified Theory of Acceptance and Use of Technology), originally developed by Venkatesh et al. (2003) was applied. It was research procedures, epistemologically positivist, quantitative method and deductive approach to exploratory and descriptive purpose. It was conducted a literature survey of topics on information systems, information technology in organizations, the context of public service and acceptance and use of technology. The field research it was used the survey method, with the data collection conducted by a questionnaire applied to active public servants of Federal University of Sergipe (UFS), which is one of at least 20 Federal Education Institutions that have adopted the same SI. The initial hypothesis of this study argued that the acceptance and use of the SI in question is influenced by four factors: Performance expectancy, Effort expectancy, Social influence and Facilitating conditions. Were added to the moderating variables: gender, age, experience and voluntariness. The sample was of 373 respondents. Treatment and data analysis were performed using descriptive analysis, confirmatory factor analysis, the t test and Analysis of Variance (ANOVA). It is concluded that the Performance expectancy, Effort expectancy and Social influence are factors that serve to measure the usage behavior of the public servers of UFS, but the influence of all of them occurred only positively to two of the three subsystems studied: the Integrated Wealth Management, Administration and Contracts (SIPAC) and the Integrated Management of Human Resources (SIGRH). The Integrated System Management Academic Activities (SIGAA) was only positively influenced by Performance expectancy. Moderators were considered only age and voluntariness of use to construct social influence; and experience to the effort expectancy. Other results were appointed to academic and managerial contributions.